O curso de licenciatura em pedagogia EaD da Universidade Federal de São Carlos: reflexões sobre o currículo - Fonseca, Ione Barbosa (2022)
The objective of this work was to discuss the curriculum of the degree course in EaD pedagogy at the Federal University of São Carlos in the light of National Curriculum Guidelines and data contained in studies selected in the State of Knowledge on the theme of distance education. In that case, they are axes of reflection: a) advances in the EaD area for the formation of pedagogues, b) permanence and c) ruptures in relation to the curriculum. The methodology used in this work focused on the qualitative approach, based on a bibliographic survey on the subject, analysis of the legislation on the regulation of the distance modality in the country, from the Law of Guidelines and Bases of Education-LDBEN to the implementation of courses of teacher training in the distance education modality in the early 2000s. The scope of the research focuses, from the specialized literature, on the discussion between points and counterpoints of the social and educational arrangements that cross-cut public policies regarding the training of the pedagogue by Distance Education and how these influence the construction of the curriculum and its actions. This research is characterized in the axis of the State of Knowledge Type, in a limited time frame, from 2000 to 2020, the routing of this work is based on the data provided by the selected studies in order to emphasize the advances and permanencies that configure the course’s curricular structure degree in EaD for the training of basic education teachers, the pedagogue, are the object of this temporal axis, as well as the location of ruptures amidst the counterpoints, delimiting the legal arrangements or milestones for the provision of Ead for the formation of the pedagogue and 2020 as upper axis that states the emphasis on training, after the promulgation of the New DCNs for the training of pedagogues and its influence or not in the distance education modality. The research showed that distance education, through the public university, teachers and tutors can be configured as a significant dimension by favoring the construction of learning communities, whether in the virtual classroom or in the training of trainers. that contribute to the initial training of teachers and keep the debate on the construction of the curriculum for distance education on the agenda for society and government.